IMPLIKASI PENGHAPUSAN VERIFIKASI BPHTB TERHADAP PENDAPATAN DAERAH - Fajaruddin Hukum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
ABSTRACT Bea Perolehan HakAtas Tanah dan Bangunan (BHPTB) or Tax on Acquisition of Land and Building is a local tax arising as a result of an act or legal events that resulted in obtaining rights to land and/or buildings by private persons or entities, and the right to land and/or building is a total right to land, including rights management and building on it, as referred to in the legislation in land and buildings (Vide; Clause 1 No. 42 dan 43 UU 28/2009). Technically, voting BPHTB further stipulated in local legislation in each local government district/city. One of the  rules set  out in the  regulation  as a  policy  associated verification  BPHTB calculation. At the same time the Ministry of Agricultural and Spatial/BPN together with a number of departments issued a joint decree of the Minister of Finance, Minister of the Internal Affairs and Director of National Land Affairs Agency(BPN) with No. SE-12/MK.07/2014,593/2278/SJ  and 4/SE/V/2014 dated May 6,2014 on Guidelines for Polling BPHTB In Relation With Land Rights Registration or Transfer of Rights to Land Registration wrong the article mentions BPN not prerequisite verification of counting in polling BPHTB. The implications are then raised in the regulation are open wide gap to the possibility of manipulation of the value of the land rights that affected the decline in local revenues from the tax sector of BPHTB. Keywords: Application, verification, local revenue, regional income.